2006
DOI: 10.1080/14034940600595621
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body fatness and physical activity on cardiovascular risk: Risk prediction using the bioelectrical impedance method

Abstract: BF% is a risk factor for CE, ischaemic stroke, and CVD mortality. An interaction between BF% and sex suggests that BF% is a stronger CVD risk factor in women. The raised cardiovascular risk associated with high BF% is reduced by physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 29 publications
0
60
0
5
Order By: Relevance
“…A previous study within the MDC study has observed that the increased relative risk for cardiovascular disease mortality with higher body fat % was reduced by leisure-time physical activity. 22 Our results indicate that this group probably needs even higher degree of physical activity in order to decrease mortality. It is however important to with fat intake were adjusted for age, sex, energy intake, season and diet method version.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A previous study within the MDC study has observed that the increased relative risk for cardiovascular disease mortality with higher body fat % was reduced by leisure-time physical activity. 22 Our results indicate that this group probably needs even higher degree of physical activity in order to decrease mortality. It is however important to with fat intake were adjusted for age, sex, energy intake, season and diet method version.…”
Section: Discussionmentioning
confidence: 81%
“…History of coronary event or stroke was identified through local and national registries. 22 Individuals with dietary change in the past are suspected to have unstable food habits. 23,24 Dietary change in the past (yes/no) was derived from the questionnaire item: 'Have you substantially changed your eating habits because of illness or for some other reason?'…”
Section: Other Variablesmentioning
confidence: 99%
“…The results are interesting both from an economic point of view and from the point of view of consumer's health. Studies have demonstrated that such higher lean-to-fat ratios improve overall health profile and reduce risk of heart attack, stroke and death from cardiovascular diseases in humans (Calling et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…5 The magnitude of the inverse association with CVD was generally similar to that observed for CHD. These studies of CVD were conducted in the United States (7 studies), 19,[42][43][44][45][46][47] Finland (3), 34,48,49 the United Kingdom (3), 30,50,51 Germany (2), 52,53 Sweden (2), 54,55 Norway (1), 41 Canada (1), 38 and China (1). 56 These studies included Ͼ68 000 men and Ͼ347 000 women in gender-specific analyses and Ͼ88 000 men and women in analyses that combined both genders.…”
Section: Magnitude Of the Associationmentioning
confidence: 99%